IMPLEMENTASI KONSEP ECODRAIN PADA EVALUASI SISTEM DRAINASE PERKOTAAN (STUDI KASUS SUB SISTEM KALI TENGGER KABUPATEN GRESIK) - Subakti, Nendi; Chalid, Abdul; Avianta, Adhi Yanuar (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Sangga Buana, 2024)
The development of urban areas is faced with increasing population and growth of building infrastructure which has a negative impact on urban spatial planning, such as the potential for flooding and inundation during the rainy season. One effort to overcome this problem is by implementing a sustainable urban drainage system in various forms of structures, including at the study location. This research aims to determine the capacity of existing drainage channels and determine alternative conservation-based flood management. The method used is to carry out hydrological analysis on the Tengger River Drainage Sub System and hydraulic analysis with SWMM 5.2 software for modeling rain runoff. The design rainfall simulation uses daily rainfall data from Suci station for 10 years (2009-2018). Model calibration using the RMSE method obtained a value of 0.053209. The modeling results found that 4 sections of existing secondary channels were at maximum capacity and overflowed with rain with a design return period of 5 years. Three alternatives were implemented at the study location, namely (1) rainwater harvesting and infiltration wells, (2) cross wave storage and (3) retention ponds. From the analysis, the most effective treatment in reducing flooding and more likely to be implemented was selected, namely implementing cross wave storage at 33 points. The eco-drain facility has a large enough storage capacity and a wider surface area to absorb water into the ground. Implementing a retention pond at the research location is difficult due to limited land, even though it reduces flood discharge better than other alternatives.